1. Determinants of technical efficiency of rice farming in dryland area of Central Lombok: An application stochastic frontier production function - I Gusti Lanang Parta Tanaya (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2007)
Abstrak Pertanian memainkan peranan penting dalam pembangunan ekonomi di negara-negara berkembang termasuk Indonesia. Padi merupakan tanaman pangan utama untuk pertanian di Indonesia sebab beras merupakan makanan pokok bagi penduduk negara ini. Walaupun produksi padi secara nasional meningkat, produktifitas per satuan input menurun. Hal ini sangat erat kaitannya dengan efisiensi produksi. Studi ini menampilkan ukuran langsung dari efisiensi produksi menggunakan fungsi produksi stokastik frontier dan model pengaruh inefisiensi. Hasil studi menunjukkan bahwa terdapat efisiensi tinggi yang rata-rata 86,75 persen dalam penggunaan input usahatani. Faktor penentu tingkat efisiensi ini adalah umur, pendidikan, pengalaman berusahatani, ketersediaan kredit, lokasi usahatani dan jumlah tenaga kerja dalam keluarga. Abstract Agriculture plays important role in economic development for most developing countries including Indonesia. Rice is a main crop for agriculture in Indonesia because it is a staple food for the populations. Even though rice production nationally increases, the productivity per input uses basis decrease. This issue is related to production efficiency. This study provides a direct measure of production efficiency using a stochastic production frontier and inefficiency effects model. The result shows that there is high level efficiency in using farm input with on average 86.75 percent. The efficiency differences can be explained by age, education, experience, credit availability, farm location and number of family labour.